Pendekatan Cart untuk Mendapatkan Faktor yang Mempengaruhi Terjangkitnya Penyakit Demam Tifoid di Aceh Utara - Yuanita, Dina; Akbar, Muhammad Sjahid; Harini, Sri (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2010)
Typhoid fever is a disease caused by Salmonella typhi bacteria. It is attack the digestive tract. Typhoid fever caused by poor sanitation and personal hygiene is not good. According to the Basic Health Research in 2007 showed that the prevalence of typhoid fever in Indonesia of 1.6%. NAD Province is hight typhoid fever prevalence(2,96 %). Because Having traced the biggest contributor was derived from NAD. Therefore, theresearch conducted to find factors that influence the outbreak of typhoid fever in NAD. research using the CART Method. The results of the analysis indicate that the main factor causing typhoid fever was drinking water reservoirs. The other factors are waste water reservoirs, the physical quality of drinking water, a habit washing hands with soap before eating, the bowel, the dump, gender, socioeconomic status, habits of washing hands with soap after defecation and health education.